Research Trends in Peace Education as A Pillar in Creating A Safe and Comfortable Learning Environment: A Bibliometric Study - Anif Istianah; Cecep Darmawan; Dadang Sundawa; Susan Fitriasari; Amjad Shamim (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: Diversity is inevitable in every community, including the school environment. By weaving diversity together, schools can create safe, respectful, and supportive spaces, allowing every student to feel accepted and valued. This study examines trends in peace education research as a pillar for creating safe and comfortable learning environments. Method: Using bibliometric analysis, the study reviews data from the Scopus database covering the period from 2019 to 2024, with keywords such as